Developing Engklek Literacy Media to Improve the Phonological Skills of 5–6-Year-Old Children at Telkom Rancaekek Kindergarten - Yeni Rahmayanti; Imamah Imamah; Chandra Apriyansyah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Phonological ability is an important foundation for early childhood reading and writing readiness, but learning in early childhood education often takes place conventionally and does not utilize play activities. This study aims to develop Engklek Literacy Media and test its feasibility and limited effectiveness in improving the phonological abilities of children aged 5–6 years. The study used the Research and Development (R&D) method with the ADDIE model. The field test subjects were all children in group B at Telkom Rancaekek Kindergarten, consisting of Group B1 (28 children) and Group B2 (26 children). Both groups were positioned as two parallel implementation groups that both received media intervention. Data were collected through observation, interviews, documentation, and expert validation sheets, then analyzed descriptively and using N-Gain at the evaluation stage. The results showed that the media received a very feasible category from material experts (94%), media experts (91%), and language experts (92%) with an average feasibility of 92%. In the field test, the combined average score increased from 43 (51%) in the pretest to 59 (70%) in the posttest with an N-Gain of 39% in the moderate category. These findings indicate that the Engklek Literacy Media is feasible to use and has an indication of effectiveness in improving children's phonological abilities in the context of Telkom Rancaekek Kindergarten, although the interpretation of effectiveness needs to be done proportionally because the research design is still pre-experimental and the intervention duration is relatively short.